Analysis of Spanish fiction series about violence and sexual abuse against women through the representation of victims, aggressors and the actions of justice - Ferrer Ceresola, Rosa María (2025)
Television fiction has the function of reflecting everyday situations, making social problems visible or addressing issues that have an impact on the collective imagination. The research presented here analyzes Spanish fiction series broadcast between 2020 and 2024 whose main plot deals with violence and sexual abuse against women: Alba (2020, RTVE Play); Mentiras (2020, Atresmedia); El Desorden que dejas (2020, Netflix); Parot (2021, Prime Video); Intimidad (2022, Netflix); Ni una más (2024, Netflix); Noche de Chicas (2024, Disney+); Ángela (2024, Atresmedia) and Querer (2024, Movistar+). Methodology. For this purpose, a methodology focused on content analysis is carried out through the study of the construction of the victim, represented in its entirety by female characters, protagonists and co-protagonists. Likewise, the role of the aggressors, the investigators and the actions of the justice system are analyzed. Results and conclusions. The results show how the titles studied approach this type of plot from the point of view of the victim and protagonist of the story. However, traditional features are still found in the construction of the characters that should be removed from the audiovisual stories. Original contribution. This research contributes to studies on gender perspective and to the analysis of the construction of female characters in television fiction as victims of acts of violence and abuse against women.